The effects of distributed and focused attention on rapid scene categorization. Issue 6 (3rd July 2018) - Brand, John; Johnson, Aaron P.
ABSTRACT: It has been argued that distributed attention facilitates the rapid extraction of summary statistics that underpins rapid scene categorization. We directly examined this hypothesis by investigating whether distributed or focused attention is more compatible with the extraction of both summary statistics (Experiment 1) and semantic scene information (Experiments 2–4). Experiment 1 replicated Chong and Treisman's (2005a) result that mean circle size judgments are more compatible with a distributed attention task than a focused attention task. Experiment 2 investigated whether this finding extends to simple scene categorization by replacing the averaging task with an animal detection task. Consistent with Experiment 1, the ability to detect the presence of an animal was more compatible with a distributed attention task than a focused attention task. Experiments 3 and 4 addressed whether distributed attention influences scene categorization tasks. When observers were asked to classify scenes based on their basic level (e.g., beach or forest; Experiment 3), there was no statistically significant difference between focused and distributed attention task conditions; however, superordinate level categorization (e.g., natural or manmade; Experiment 4) was faster when combined with a task requiring distributed attention compared to a task requiring focused attention.